2023
DOI: 10.1038/s41598-022-27138-2
|View full text |Cite
|
Sign up to set email alerts
|

Peak Cenozoic warmth enabled deep-sea sand deposition

Abstract: The early Eocene (~ 56–48 million years ago) was marked by peak Cenozoic warmth and sea levels, high CO2, and largely ice-free conditions. This time has been described as a period of increased continental erosion and silicate weathering. However, these conclusions are based largely on geochemical investigation of marine mudstones and carbonates or study of intermontane Laramide basin settings. Here, we evaluate the marine coarse siliciclastic response to early Paleogene hothouse climatic and oceanographic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…As discussed above, PetroMod™ assumes that methane entering the GHSZ and exceeding the solubility limit is instantaneously converted to hydrate, and therefore does not consider the kinetically feasible coexistence of hydrate and free gas phases within the GHSZ (Burwicz et al., 2017) or, for instance, the migration of gas through the GHSZ, invoked at Blake Ridge (Gorman et al., 2002). We make various assumptions by assigning model boundary conditions, as detailed above, including the assumption of constant basal heat flows, sediment‐water interface temperatures, and water depths through time, and we do not explicitly consider, for instance, impacts of sea‐level fluctuations on variable delivery of organic matter or coarse‐grained sediment to our real‐world model areas (e.g., Blum & Hattier‐Womack, 2009; Burton et al., 2023; Erbacher et al., 1996), though we do seek to replicate coring‐ and geophysical data‐based interpretations of stratigraphy and lithology, as detailed above.…”
Section: Methodsmentioning
confidence: 99%
“…As discussed above, PetroMod™ assumes that methane entering the GHSZ and exceeding the solubility limit is instantaneously converted to hydrate, and therefore does not consider the kinetically feasible coexistence of hydrate and free gas phases within the GHSZ (Burwicz et al., 2017) or, for instance, the migration of gas through the GHSZ, invoked at Blake Ridge (Gorman et al., 2002). We make various assumptions by assigning model boundary conditions, as detailed above, including the assumption of constant basal heat flows, sediment‐water interface temperatures, and water depths through time, and we do not explicitly consider, for instance, impacts of sea‐level fluctuations on variable delivery of organic matter or coarse‐grained sediment to our real‐world model areas (e.g., Blum & Hattier‐Womack, 2009; Burton et al., 2023; Erbacher et al., 1996), though we do seek to replicate coring‐ and geophysical data‐based interpretations of stratigraphy and lithology, as detailed above.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that the target reservoir is buried deep, the horizontal difference stress coefficient is applicable to represent the influence of horizontal stress difference on FI. The calculation method is shown in Equation (9). A small difference coefficient of horizontal stress is beneficial to reservoir fracturing.…”
Section: Horizontal Stress Difference Coefficientmentioning
confidence: 99%
“…In contrast, riverine detrital material could have affected the IC3 scores. It has been reported that the contribution of terrigenous fluvial input into the deep-sea sediments around the continent has increased during the earliest Eocene and EECO (Burton et al, 2023). Thus, enhanced denudation, drainage, and chemical weathering in the warm and humid terrestrial environment in the early Eocene may have caused an increase in riverine input of terrigenous materials to the coastal area and, thus, low values in the IC3 score at Site 762C.…”
Section: Ic4: Diagenetic Signature On Carbonatementioning
confidence: 99%